ADULT EDUCATION FOR MARGINALIZED GROUPS: ISSUES AND INTERVENTIONS - SAID , KALTUME SHARIF (Sokoto Educational Review, 2025)
Adult education involves adults participating in systematic and ongoing self-education to acquire knowledge, skills, attitudes, or values, with the goal of addressing societal socio-economic, cultural, political, and environmental challenges. Unfortunately, marginalized groups like girls, women, rural residents, people with disabilities, internally displaced persons (IDPs), the elderly, and low-income earners often face significant systemic barriers to accessing these opportunities. This paper critically assesses adult education for these marginalized groups, considering various challenges and intervention programs. Based on an exploratory survey relying on secondary data from articles, journals, newspapers, and magazines, the study identified key issues hindering access, including inadequate infrastructure, insufficient funding, corruption, unaffordable costs, individual learner differences, armed conflicts and insecurity, a lack of professional facilitators, and gender discrimination. Furthermore, the study highlighted several intervention programs, such as community-based and mobile learning, incentives and cash transfers, inclusive infrastructure and training, language diversification, awareness campaigns, and technology integration. The paper concludes that marginalized groups have limited access to education and can be better supported through adult and non-formal education initiatives. DOI: https://doie.org/10.10318/SER.2025503853